The Effect of Zinc Supplementation on Malondialdehyde (MDA) Levels in First Year Students of The Faculty of Medicine Universitas Pattimura - Tuanaya, Syafira Arfani; Angkejaya, Ony W; de Lima, Filda Vionita Irene; Abbas, Mutmainnah; Tamalsir, Dylan; Sulfiana (Biomedika, 2024)
An imbalance between free radicals and antioxidants in the body causes a condition called oxidative stress, which can be caused by several factors, one of which is psychological stress. Various studies have shown that medical students tend to experience psychological stress, especially in first year. Psychological stress tends to increase SO conditions due to increased ROS and free radicals in the body. Zinc can reduce ROS and free radicals through several mechanisms. This study aims to determine the effect of zinc supplementation on MDA levels in first year students of the Faculty of Medicine. This study used a true experimental analytic study with pretest-posttest control group design. The sample amounted to 22 people in intervention group and 22 people in control group. This study used TBARS method to measure MDA levels. The results showed a decrease in MDA levels in intervention group (p=0.000), while in the control group there was an increase in MDA levels (p=0.006). In addition, lower MDA levels were found in intervention group compared to control group measured after 10 days (p=0.000). This study concluded that there was an effect of Zinc supplementation on MDA levels in first year students of the Faculty of Medicine, Pattimura University.